The octamer motif is a B-lymphocyte-specific regulatory element of the HLA-DR alpha gene promoter. - Sherman, P A (1989)
The human class II gene, HLA-DR alpha, contains an octanucleotide sequence ATTTGCAT located approximately 40 base pairs upstream of the transcription initiation site. We have investigated the transcriptional function of the DR alpha octamer in human B-lymphoblastoid cells and non-B cells. Deletion and substitution mutagenesis of the octamer sequence greatly reduced the activity of the DR alpha promoter in both in vivo and in vitro cell-free transcription systems of B-cell origin. Conversely, these mutations did not affect promoter activity in several non-B-cell lines that express the DR alpha gene. Removal of octamer-binding proteins by in vivo titration with an octamer-containing competitor plasmid reduced DR alpha promoter activity in B-lymphoblastoid cells. These results suggest that a protein-octamer interaction, most likely involving the B-cell-specific octamer binding protein (OTF-2), is required for DR alpha promoter function in B-lymphoblastoid cells but not in non-B cells.